Questionário de qualidade de vida específico para Rosácea: tradução, adaptação cultural e validação para o Português do Brasil - Tannus, Flavia Cisi [UNIFESP] (2017)
Aim: translation into Brazilian Portuguese, development of cultural adaptation and validation of the RosaQoL disease-specific questionnaire through the participation of individuals that were diagnosed with Rosacea of any subtype. Methods: recommended procedures for translation, cultural adaptation and validation of an instrument were followed, and three interviews were performed: baseline (n = 60); second (from 7 to 14 days after baseline, n=46) and third (from four to six months after baseline, n=38). In the first one, the SF-36 and RosaQoLBR (Brazil) were applied, in the others only RosaQoL-BR. Psychometric measures were analyzed: reliability by internal consistency (Cronbach’s alpha); test-retest reproducibility (intraclass correlation coefficient); responsiveness by the Wilcoxon test, comparing the interviews and third and validity, by correlations, comparative analysis and variance. Results: terms of the original questionnaire were replaced to guarantee cultural and semantic equivalence. The validity can be demonstrated by the expressive correlations between the RosaQoL-BR domains and significance in the Jonckheere-Terpstra test (p< 0.05) between the scores of the RosaQoL-BR domains and the self-perception of the participants in relation to the disease. Reliability was acceptable; alpha coefficient ranged from 0.923 to 0.916 in the first and second applications of the RosaQoL-BR, respectively, and the Intraclass Correlation Coefficient (ICC) ranged from 0.671 to 0.863 in the range of seven to fourteen days. Responsiveness, measured by the formation of three groups of participants based on self-perception of rosacea (better, worse, or unchanged), was found to be significant in the "best" response group (p< 0.05). Limitations: small sample; clinical variability of rosacea due to the few sources of screening of participants. Conclusions: RosaQoL-BR has been shown to be a reliable, valid and responsive questionnaire for individuals with any subtype of rosacea, with limitations.